Understanding the Concept of the Rule of Law of Timor-Leste - Lulo, Lourenço de Deus Mau (Recent Research Advances in Arts and Social Studies Vol. 8, 2024)
A Nation is a collection of people who are bound for the unity of language and certain regions on earth. Thus the people of Timor-Leste is a group of people who have the same interests and assert itself as a nation, and proceeding in a region. The regulatory authority stipulated the establishment of the State of Law in Timor- Leste, is constitutionally under the Constitution only set the key things that are abstract, while things that are more concrete set in the form of the Act. However, based on the Constitution of the setting material different payloads in the Constitution, because the regulation concerning the substance of the general nature of abstract and general nature Concrete has been specified in the constitution. Consequently, in its application, directly apply the Constitution. Therefore matters relating to the public interest have been set directly in the Constitution. The Constitution outlines the general principles for forming a government at the national level, but it's the underlying laws that actually put those principles into action.